Theatre Royal, under the management of Messrs. Williamson, Garner & Musgrove, leasee Mr. Saml. Lazar, treasurer Mr. Geo. L. Goodman : return of the favourite comedian, Mr Bland Holt, who will have the honour of inaugurating his annual dramatic season with his own specially organised company in his latest novelty, The Ruling Passion, an entirely exciting sensational drama, full of thrilling situations. Scenery by Geo. Gordon illustrating London by daylight, gaslight and moonlight, including the perilous balloon ascent and a London street during a storm of real rain (as originally produced in the play). Saturday, May 25th, '89 will be produced for the first time in Sydney, The Ruling Passion, written by Mr James Willing. - Holt, Bland, 1851-1942; Bishop, Kate, 1848-1923; Willing, James, 1837 or 1838-1915; Williamson, J. C. (James Cassius), 1845-1913; Garner, Arthur, born 1851; Musgrove, George, 1854-1916; Gordon, George, 1839-1899; Theatre Royal (Castlereagh St., Sydney, N.S.W.); Williamson, Garner & Musgrove; J.C. Williamson (Firm) ([Sydney] : Theatre Royal, 1889)
Broadside advertising a production at the Theatre Royal, Sydney. Text in red and blue on a buff background. Title appears in large diagonal hand cut wood type at the centre. The text continues with a "list of persons represented with their characteristics and ruling passions" below. Other principal performers include: Charles Holloway, Albert Norman, Walter Howe, Wilmot Eyre, Augustus Glover, B. N. Jones, Blanche Lewis, Virginiana Vivienne, May Vivienne, Kate Bishop, Flora Anstead, Gertie Palmer, and Mrs Bland Hold. A list of the five acts and tableaus appears next, followed by a special notice (about Bland Holt's appearances and the management's policy relating to changes of bill), with pricing details and credits at the bottom edge.
Caption title.
Library's copy is stamped: The Property of J. C. Williamson, Ltd. It was formerly catalogued at PA Broadside 61.
Also available online
Ephemera (PROMPT Collection): [Holt, Bland (actor/manager) : programs and related material collected by the National Library of Australia].
Ephemera (PROMPT Collection): J.C. Williamson.
Manuscript Collection: Papers of Bland Holt, 1880-1928, MS 2244.
Keywords: Holt, Bland, -- 1851-1942 -- Posters; Theatre Royal (Castlereagh St., Sydney, N.S.W.) -- Posters; J.C. Williamson (Firm) -- Posters; Theatrical posters, Australian; Advertising -- Performing arts -- Australia -- Posters; Broadsides -- Australia; Australian